PERAN GURU DALAM MENGATASI STRESS AKADEMIK TERHADAP ANAK USIA DINI - Aulia Septianti Putri; Sondang Nauli; Aulia Safira Putri; Murni Noer Chasanah; JIlan Maulidya Rullo (UNIVERSITAS SERAMBI MEKKAH, 2024)
The success of education lies in the extent to which teachers use their abilities in educational practice. This research uses a qualitative approach using case studies. The subjects of this research were kindergarten teachers. Data were collected using observation and interviews. Analysis of research data using grounded theory. Test the validity of research data using triangulation of sources and techniques. The results of this research show that young children experience stress due to pressure from parents or guardians who want their children to be able to CALISTUNG (Reading, Writing and Counting). The obligation for school principals and teachers to fulfill the demands of parents or guardians of kindergarten students. In addition, the Kindergarten Principal gives various tasks to teachers. The findings of this research contribute to knowledge regarding the causes of academic stress in early childhood and recommend early childhood education institutions to minimize the occurrence of stress in children.